EARLY-RIPENNING POTATO IN DUAL CROPPING - E. L. Semenchenko; T. V. Semibratskaya (Овощи России, 2015)
The most effective types of treatments of freshly harvested potato tubers for dual cropping in conditions of irrigation of North steppe of Ukraine were determined. For the cv. Impala it is a pretreatment by water solution of Fumar and Gibberellin, water solution of Reastim and Gibberellin. For the cv. Zagadka it is a pre-treatment by water solution of Reastim and Gibberellin.